2001
DOI: 10.1038/sj.cdd.4400917
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of monoglycerides as apoptotic agents in T-cells

Abstract: Recently, lipids have received considerable attention for their potential to induce apoptosis when added exogenously to cells. In this study, we directly demonstrate that murine T-cells undergo rapid apoptosis following treatment with various forms of monoglycerides, which are a family of naturally occurring lipids consisting of a single fatty acid moiety attached to a glycerol backbone. The potency of these lipids varied depending on their chemical structure, whereas glycerol backbone or corresponding fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Free FA (FFA) and sn-2-monoacylglycerol (sn-2 MAG), the two hydrolysis products of dietary TAG, are absorbed from the lumen into polarized enterocytes in the small intestine. Polyunsaturated FAs (PUFAs) are better absorbed when they are esterified at the sn-2 position of the glycerol molecule, while the type of FA at the remaining locations also influences their intestinal absorption [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Free FA (FFA) and sn-2-monoacylglycerol (sn-2 MAG), the two hydrolysis products of dietary TAG, are absorbed from the lumen into polarized enterocytes in the small intestine. Polyunsaturated FAs (PUFAs) are better absorbed when they are esterified at the sn-2 position of the glycerol molecule, while the type of FA at the remaining locations also influences their intestinal absorption [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that monoglycerides induce apoptosis in murine cells 5 and wanted to examine the cytotoxicity of monoglycerides on malignant and normal human cells. We first evaluated the death-inducing potential of monoglycerides in a panel of human leukemic cell lines ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…As described previously, 5,12 assays for apoptosis were the following: loosening of membrane phospholipids, measured with merocyanin-540 (MC540; Molecular Probes, Eugene, OR); phosphatidylserine exposure, assayed by FITCor biotin-conjugated annexin V followed by Quantum Red-conjugated streptavidin (BD BioSciences); retention of vital dyes, detected with propidium iodide (PI; Sigma-Aldrich); and DNA degradation, measured with the TdT-dependent dUTP-biotin nick end-labeling (TUNEL) assay.…”
Section: Drug Treatment Antibodies and Apoptosismentioning
confidence: 99%
See 2 more Smart Citations